Effect of replacing groundnut cake with dried Moringa oleifera leaves on growth and nutrient utilization in crossbred (Hampshire × Ghungroo) grower pigs - BARMAN, KESHAB; BANIK, SANTANU; THOMAS, RANJENDRAN; KUMAR, SUNIL; DAS, ANIL KUMAR; DUTTA, KARABEE; RAJKHOWA, SWARAJ (The Indian Journal of Animal Sciences, 2021)
The objective of this study was to evaluate the effect of replacement of groundnut cake with dried Moringa (Moringa oleifera) leaves on growth and nutrient utilization in crossbred grower pigs. Eighteen crossbred (Hampshire × Ghungroo) grower pigs (about 2 months old, body wt. 12–14 kg) of either sex were divided into three groups of six each in a randomized block design. Three different diets were used for feeding of the animals. These were namely, T1 (standard grower ration without dried Moringa leaves), T2 (standard grower ration supplemented with 5% dried Moringa leaves by replacing groundnut cake) and T3 (standard grower ration supplemented with 10% dried Moringa leaves by replacing groundnut cake). The pigs were fed on the experimental grower rations twice daily in the morning and evening. The crude protein content (% DM) of the grower ration ranged from 18.82±0.08 to 20.36±0.06 while that of Moringa leaves was 15.11±0.73. The average dry matter intake was (kg/d) 0.62, 0.62 and 0.60 respectively in T1, T2 and T3 groups which were found similar across all the groups. Digestibility coefficients (%) of dry matter, organic matter, ether extract, crude fibre and nitrogen free extracts increased in Moringa supplemented groups. While crude protein digestibility was higher in T2 group in comparison to other two groups. Nitrogen balance (g/d) was positive across all the groups and values were 16.10, 16.79 and 15.38 in groups T1, T2 and T3 respectively. The absorbed N (g/d) was significantly higher in T1 group (19.23) in comparison to the other two groups. However, there was no significant difference in absorbed N (g/d) in group T1 and T2. The absorbed N as percent intake, net protein utilization and biological value were similar across all the groups. The average body weight gain (g/day) was higher in Moringa leaves supplemented groups. The cost (`````₹/kg gain) was reduced in T2 and T3 groups in comparison to T1. The feed conversion ratio (FCR) was higher in group T3 and lower in T2 group. From this study, it is concluded that dried Moringa leaves can be supplemented @ 5% level by replacing groundnut cake in grower crossbred pigs for better growth, nutrient utilization, feed conversion efficiency and also to lessen the feed cost.